Attraction, Lyapunov stability and orbital maps for semigroup actions on topological spaces and fiber bundles - Rocha, Victor H. L. [UNESP] (2022)
This paper aims to study orbital maps in the context of semigroup actions on topological spaces and fiber bundles. It presents results on the behavior of the dynamical objects involved in the theories of attraction and Lyapunov stability under orbital maps. It also presents results on orbital maps in the context of semigroups acting on the fibers of a fiber bundle.